9 3/7 would be your answer
Answer:
![a_n=\frac{-1}{2}a_{n-1}](https://tex.z-dn.net/?f=a_n%3D%5Cfrac%7B-1%7D%7B2%7Da_%7Bn-1%7D)
![a_1=2](https://tex.z-dn.net/?f=a_1%3D2)
Step-by-step explanation:
The recursive rule is a term defined in terms of other terms in the sequence.
The is a geometric sequence because it has a common ratio.
The common ratio can be found by dividing a term by previous term.
For example, all of these are equal:
![\frac{-1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-1%7D%7B2%7D)
![\frac{\frac{1}{2}}{-1}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7B1%7D%7B2%7D%7D%7B-1%7D)
![\frac{\frac{-1}{4}}{\frac{1}{2}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7B-1%7D%7B4%7D%7D%7B%5Cfrac%7B1%7D%7B2%7D%7D)
They are all equal to
.
So we are saying:
![\frac{\text{term}}{\text{previous term}}}=\frac{-1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Ctext%7Bterm%7D%7D%7B%5Ctext%7Bprevious%20term%7D%7D%7D%3D%5Cfrac%7B-1%7D%7B2%7D)
More formally:
.
Multiply both sides by
:
![a_n=\frac{-1}{2}a_{n-1}](https://tex.z-dn.net/?f=a_n%3D%5Cfrac%7B-1%7D%7B2%7Da_%7Bn-1%7D)
When doing recursive form, you need to state a term of the sequence (or more depending on the recursive form you have).
So the first term is 2.
So the full thing for the answer is:
![a_n=\frac{-1}{2}a_{n-1}](https://tex.z-dn.net/?f=a_n%3D%5Cfrac%7B-1%7D%7B2%7Da_%7Bn-1%7D)
![a_1=2](https://tex.z-dn.net/?f=a_1%3D2)
For 121212 guests we need 555 liters,for 363636 guests how many liters
Guests Soda
121212 555
363636 x
So 121212*x=363636*555
x=363636*555/121212
x=555*3
x=1665